Women Who Sexually Offend Display Three Main Offense Styles: A Reexamination of the Descriptive Model of Female Sexual Offending. (June 2014) - Gannon, Theresa A.; Waugh, Greg; Taylor, Kelly; Blanchette, Kelly; O'Connor, Alisha; Blake, Emily; Ó Ciardha, Caoilte
This study examined a theory constructed to describe the offense process of women who sexually offend—the Descriptive Model of Female Sexual Offending (DMFSO). In particular, this report sets out to establish whether the original three pathways (or offending styles) identified within United Kingdom convicted female sexual offenders and described within the DMFSO (i.e., Explicit-Approach, Directed-Avoidant, Implicit-Disorganized) were applicable to a small sample ( N = 36) of North American women convicted of sexual offending. Two independent raters examined the offense narratives of the sample and—using the DMFSO—coded each script according to whether it fitted one of the three original pathways. Results suggested that the three existing pathways of the DMFSO represented a reasonable description of offense pathways for a sample of North American women convicted of sexual offending. No new pathways were identified. A new "Offense Pathway Checklist" devised to aid raters' decision making is described and future research and treatment implications explored.